1989
DOI: 10.1159/000242913
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Renal Adenylate Cyclase Receptor System to Parathormone during the Last Third of Pregnancy in the Rat

Abstract: During the last third of pregnancy, the rat phospho-calcic metabolism is clearly modified. Sensitivity of the renal receptor to parathormone (PTH) was investigated over this period in the fetuses and their mothers. As early as day 16.5 of pregnancy, the fetal kidney is sensitive to bovine PTH (1–34) on the basis of cAMP production. Sensitivity declines on the last day of pregnancy. The newborn kidney showed a higher response to PTH 3 h after birth than after 24 h. The basal adenylate cyclase activity in renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…They are also comparable with those obtained in the rat [29], This latter work showed that the adenylate cyclase system in the renal membrane, which incorporates the Gs protein without isolating it, must be func tional in the fetus in útero during the last tri mester. It would also suggest that renal resis tance may be linked with a receptor desensiti zation phenomenon with resulting parathy roid hormone excess due to the drop in serum calcium levels observed in preterm infants.…”
Section: Discussionsupporting
confidence: 84%
“…They are also comparable with those obtained in the rat [29], This latter work showed that the adenylate cyclase system in the renal membrane, which incorporates the Gs protein without isolating it, must be func tional in the fetus in útero during the last tri mester. It would also suggest that renal resis tance may be linked with a receptor desensiti zation phenomenon with resulting parathy roid hormone excess due to the drop in serum calcium levels observed in preterm infants.…”
Section: Discussionsupporting
confidence: 84%